2019
DOI: 10.3390/jcm8101613
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Function in Peripheral Blood Mononuclear Cells (PBMC) Is Enhanced, Together with Increased Reactive Oxygen Species, in Severe Asthmatic Patients in Exacerbation

Abstract: Asthma is a chronic inflammatory lung syndrome with an increasing prevalence and a rare but significant risk of death. Its pathophysiology is complex, and therefore we investigated at the systemic level a potential implication of oxidative stress and of peripheral blood mononuclear cells’ (PBMC) mitochondrial function. Twenty severe asthmatic patients with severe exacerbation (GINA 4–5) and 20 healthy volunteers participated at the study. Mitochondrial respiratory chain complexes activities using different sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 43 publications
0
12
0
2
Order By: Relevance
“…With emerging evidence on the possible links between allergy and neurodevelopment disorders, it is important to understand the underlying mechanisms so as to identify new treatment and therapeutic targets. To further elucidate the role of epigenetics ( 111 , 114 ) and mitochondrial dysfunction ( 119 , 122 ) in contributing to the link and development of allergy and ADHD and ASD, more in vivo studies are required to examine the methylation pattern and ETC complex activities in animal models that are reflective of the conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With emerging evidence on the possible links between allergy and neurodevelopment disorders, it is important to understand the underlying mechanisms so as to identify new treatment and therapeutic targets. To further elucidate the role of epigenetics ( 111 , 114 ) and mitochondrial dysfunction ( 119 , 122 ) in contributing to the link and development of allergy and ADHD and ASD, more in vivo studies are required to examine the methylation pattern and ETC complex activities in animal models that are reflective of the conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Raby et al reported a significant association between mitochondrial haplotype and total serum IgE levels and that haplogroup U carriers had greater skin prick test reactivity and higher rate of AD ( 118 ). A recent study by Ederle et al showed that peripheral blood mononuclear cells (PBMCs) of severe asthmatic patients had increased mitochondrial respiratory chain complexes activity and ROS production than had PBMCs of healthy subjects ( 119 ). Mitochondrial dysfunction in the form of reduced cytochrome c expression and activity and decreased lung ATP levels was observed in ovalbumin (OVA)-induced experimental allergic asthma mice, and anti-inflammatory IL-4 antibody treatment was able to reverse the mitochondrial dysfunction, indicating a link between mitochondrial dysfunction and inflammation in allergic asthma ( 120 ).…”
Section: Possible Mechanisms Linking Allergy and Neurodevelopmental Dmentioning
confidence: 99%
“…Alternatively, peripheral blood mononuclear cells (PBMCs) and/or platelets represent an easily available population of cells allowing mitochondrial function studies. Analysis of the energetic profile (mitochondrial function) of circulating blood cells in experimental animals and humans appears as a new research field with potential applications in the development of disease biomarkers in several settings, including respiratory and CVDs [10][11][12][13][14]19,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…For the evaluation of complexes II, III and IV (Vsucci), succinate was injected (25 mmol/L). The addition of rotenone (0.5 mmol/L) allowed the calculation of Vrot, which represents complexes II, III, IV and V activities [ 31 ]. For the evaluation of cytochrome c oxidase (complex IV) separately (Vtmpd), N,N,N′,N′-tetramethyl-p-phenylenediamine dihydrochloride (TMPD, 0.5 mmol/L) and ascorbate (0.5 mmol/L) were added as an artificial electron donor to cytochrome c. Finally, tissues were harvested and dried (15 min at 150 °C) and respiration rates were expressed using pmol of oxygen/second/mg of wet weight.…”
Section: Methodsmentioning
confidence: 99%